Differential perceptions of a hypothetical sexual assault survivor based on race and ethnicity: Exploring victim responsibility, trauma, and need for social support. Issue 4 (19th May 2019) - Lewis, Kaleea R.; Robillard, Alyssa; Billings, Deborah; White, Kellee
Abstract: Objective: Explore the ways in which a sample of college women interpret racially/ethnically coded vignettes to understand their perceptions of responsibility and trauma experienced by a hypothetical female sexual assault survivor and her need for social support.Participants: Convenience sample of college women ( N  = 51) attending a large, predominately white university in the Southeastern United States recruited between January and March 2013.Methods: Participants were randomly assigned one of three vignettes describing a hypothetical date rape scenario. Vignette scenarios were identical except for discrete statements coded to signify either an African American, Latina, or white female student. Participants responded to open-ended questions that gauged their interpretations of responsibility, trauma, and social support.Results: Qualitative analysis of open-ended responses revealed six overarching themes, including overt victim blaming/shaming, justification of the sexual assault, and perceived need for social support.Conclusions: Findings point to the significance of including race in discussions about and programs that address sexual assault on college campuses to ensure that all women who experience sexual violence receive the support that they need.